Use of Random Urine Samples to Estimate Total Urinary Calcium and Phosphate Excretion - Gökçe, Çiğdem; Gökçe, Özcan; Baydinç, Can; İlhan, Necip; Alaşehirli, Erhan; Özküçük, Ferhat; Arslan, Nadi (My University, 1991)
Calcium-to-creatinine and phosphate-to-creatinine ratios in random single-voided urine specimens were compared with 24hour calcium and phosphate excretions, respectively, in 67 subjects who were selected prospectively to represent a wide range of renal and parathyroid function as well as urinary calcium and phosphate loss. Simple linear regression analysis revealed significant correlation between the spot urine calcium-to-creatinine ratio and 24-hour total calcium excretion and between the spot urine phosphate-to-creatinine ratio and 24-hour phosphate excretion. Calculating these simple ratios permits easy, rapid, correct, and inexpensive estimation of the daily urinary calcium and phosphate excretion. © 1991, American Medical Association. All rights reserved.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium; Creatinine; Female; Human; Kidney Failure, Chronic; Male; Middle Age; Monitoring, Physiologic; Phosphates; Prospective Studies; Random Allocation; Reference Values; Regression Analysis; calcium; creatinine; phosphate; adolescent; adult; aged; article; calcium urine level; controlled study; female; human; kidney function; major clinical study; male; parathyroid function; phosphate urine level; priority journal; urine